Histology of non-small cell lung cancer predicts the response to stereotactic body radiotherapy. Issue 2 (November 2017) - Hörner-Rieber, Juliane; Bernhardt, Denise; Dern, Julian; König, Laila; Adeberg, Sebastian; Paul, Angela; Heussel, Claus Peter; Kappes, Jutta; Hoffmann, Hans; Herth, Felix J.P.; Debus, Jürgen; Warth, Arne; et al.
Abstract: Background and purpose: To investigate the prognostic impact of different histological subtypes of non-small cell lung cancer (NSCLC) on outcome following stereotactic body radiotherapy (SBRT) for NSCLC patients. Materials and methods: We analyzed 126 consecutive patients with early-stage adenocarcinoma or squamous cell carcinoma treated with SBRT from 2004 to 2016. Adenocarcinoma patients were further sub-classified as high-risk or low-risk tumors. Results: With a median follow-up time of 22 months, 2-year overall survival (OS), local (LC), and distant control (DC) were 68%, 90% and 79%, respectively. For LC, histologic subtype was identified as major independent prognostic factor ( p = 0.033): while LC was 81% for squamous cell carcinoma patients, LC was significantly improved for high-risk and even more non-high-risk adenocarcinoma patients with 96% and 100%, respectively ( p = 0.026). The negative prognostic impact of the histologic subtype "squamous cell carcinoma" was not evident when patients received SBRT with higher total doses in EQD2 (2 Gy equivalent dose): if patients were treated with a total dose in EQD2 ≥ 150 Gy, no significant difference in LC for histologic subtypes was detected anymore ( p = 0.355). Conclusion: In the current study, histologic subtypes of NSCLC predicted local control probabilities following SBRT. Prospective, multi-center studies are needed to evaluate the prognostic impact of histology and consecutively the need for SBRT dose adaptation.